Dukungan Suami Dalam Pencegahan Anemia Pada Kehamilan - Rachmawati, Fijri (Universitas Malahayati Bandar Lampung, 2022)
Background: More than 80% of countries in the world, the prevalence of anemia in pregnancy is > 20% and can be considered as a major public health problem. Chronic iron deficiency can affect the general well-being of both mother and baby. The indirect factor of anemia is the husband's support, the husband has a very important role for the mother, support can be given in the form of physical and psychological.Objective: To determine the relationship of husband's support in preventing anemia in pregnancy.Methodology: An analytical observational study with a cross sectional approach, which was conducted from December 2020 to February 2021. The sample size was 47 pregnant women and 47 husbands. Data analysis uses chi square, if it does not meet the requirements then use Kolmogorov Smirnov.Results: statistical test results showed that there was a relationship between husband's support in preventing anemia in pregnancy (P=0.000)Conclusion: the results of the study found that there was a relationship between husband's support in preventing anemia in pregnancy.Suggestion: Conduct counseling and IEC about the importance of nutrition during pregnancy to prevent nutritional iron deficiency anemia in pregnant women by involving husbands, families and health workers, as well as health workers to provide assistance and regular monitoring of activities that have been carried out as an effort to improve maternal nutrition. pregnant Keywords: Husband's support, Prevention of Pregnancy Anemia ABSTRAK Latar Belakang: Lebih dari 80% Negara di dunia, prevalansi anemia pada kehamilan > 20% dan dapat dianggap sebagai masalah kesehatan masyarakat yang utama. Kekurangan zat besi kronis dapat mempengaruhi kesejahteraan umum ibu dan bayi. Faktor tidak langsung anemia yaitu dukungan suami, suami memiliki peran yang sangat penting bagi ibu, dukungan dapat diberikan dalam bentuk fisik maupun psikis.Tujuan: Untuk mengetahui hubungan dukungan suami dalam pencegahan anemia pada kehamilan.Metodologi: Penelitian observasional analitik dengan pendekatan cross sectional yang dilakukan pada bulan Desember sampai bulan Februari Jumlah sampel 47 responden ibu hamil dan 47 responden suami. Analisa data menggunakan chi square.Hasil: hasil uji statistik menunjukkan bahwa ada hubungan dukungan suami dalam pencegahan anemia pada kehamilan (P=0.000)Kesimpulan: hasil penelitian didapatkan bahwa ada hubungan dukungan suami dalam pencegahan anemia pada kehamilan.Saran: Melakukan penyuluhan dan KIE tentang pentingnya nutrisi selama kehamilan untuk mencegah terjadinya anemia defesensi besi gizi ibu hamil dengan melibatkan suami, keluarga serta petugas kesehatan, serta petugas kesehatan melakukan pendampingan dan pemantauan secara rutin tentang kegiatan yang sudah dilakykan sebagai salah satu upaya meningkatkan gizi ibu hamil Kata Kunci: Dukungan suami, Pencegahan Anemia Kehamilan